The model of internationalization process : an exploratory research of Malaysian food service firms / Lim Kuang Long - Lim, Kuang Long (2012)
This thesis undertakes the research project from an inductive position to shape the result by adopting the qualitative research process. It challenges the existing theory of internationalization process. This study will compare and contrast the sequential and non-sequential stage in internationalization process. The research tries to explore the facilitation of internationalization process that allows the acceleration of Malaysian foodservice firms to expand globally. By using behavioral approach, this study identifies and delineates the components of strategies adopted in the internationalization process. Based on the case study of the three selected Malaysian foodservice firms, the new model was proposed. It asserted that the intention to expand business overseas requires a firm to undergo (1) pre-internationalization stage; (2) international entry stage; and (3) post-internationalization stage. These three stages were affected by two themes at each stage. These two themes, namely “Western Embeddedness” and “Government Influence” were in turn, formulated on the basis of twelve concepts of internationalization process in cross-case analysis. These twelve concepts were the strategies that accelerated the foreign markets penetration of Malaysian foodservice firms. It was also contended that foodservice firms expand overseas first by franchising, then exporting, and eventually setting up their plant abroad. The newly proposed model of internationalization process was then debated with the existing literature. The limitations and future directions of this model were also discussed.